Biomechanical characteristics of back double salto dismount off the uneven bars - Potop, V.; Timnea, O. C.; Mihaiu, C.; Manole, C. (Journal of Physical Education and Sport, 2014)
This paper aims at highlighting the biomechanical characteristics of the back double salto dismount off the uneven bars in women`s artistic gymnastics. This scientific approach has led to the organization of a study conducted throughout two national competitions 2012 and 2013, with a group of 6 junior gymnast`s aged 12 to 15, members of the junior Olympic team of Izvorani. The biomechanical analysis has been performed by means of Physics Toolkit program and of the movement postural orientation method, highlighting the key elements of the sports technique used in back double salto dismount off the uneven bars. The results of the study showed the anthropometric and biomechanical indicators necessary for the biomechanical analysis of the back double salto dismount off the uneven bars. The comparative biomechanical analysis of the back double salto dismount off the uneven bars highlighted the influence of the kinematic and dynamic characteristics on the technical execution in accordance with the performances achieved in competitions.